2004
DOI: 10.1086/382896
|View full text |Cite
|
Sign up to set email alerts
|

A Large Case‐Control Study of Cervical Cancer Risk Associated with Human Papillomavirus Infection in Japan, by Nucleotide Sequencing–Based Genotyping

Abstract: Using nucleotide sequencing-based genotyping, we conducted a case-control study to examine cervical cancer risk associated with human papillomavirus (HPV) infection in a Japanese population. A consensus primer pair was used to amplify DNA from the L1 region of HPV by polymerase chain reaction (PCR). By PCR, 311 of 356 patients with cervical cancer and 333 of 3249 control individuals were positive for HPV. By the direct sequencing of PCR products, nucleotide sequences of 30 genotypes were obtained. A high incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 16 publications
10
65
1
Order By: Relevance
“…Other reports using HPV genotyping tests also showed that HPV 52 was a more common genotype among Japanese individuals who had either normal cytology or cervical neoplastic lesions compared with individuals in other countries. 10,19,20 In Japan, a commercial cervical cancer vaccine finally became available after December 2009. This study has some limitations because we obtained data from pregnant women; however, our data from pre-vaccination women on the distribution of genital HPV infections in the region where HPV 52 is more prevalent are important for the understanding of the cross-reactivity of a bivalent HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports using HPV genotyping tests also showed that HPV 52 was a more common genotype among Japanese individuals who had either normal cytology or cervical neoplastic lesions compared with individuals in other countries. 10,19,20 In Japan, a commercial cervical cancer vaccine finally became available after December 2009. This study has some limitations because we obtained data from pregnant women; however, our data from pre-vaccination women on the distribution of genital HPV infections in the region where HPV 52 is more prevalent are important for the understanding of the cross-reactivity of a bivalent HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…For consistency with previous studies, we considered 16 HPV genotypes (16, 18, 31, 33, 35, 45, 51, 52, 53, 56, 58, 59, 66, 68, 73 and 82) as high-risk genotypes that are related to cervical cancer. [8][9][10] RESULTS A total of 151 women were enrolled in the study. In all, 79 women were in the first trimester of their pregnancy, 18 were in the second trimester, 51 were in the third trimester and 3 were postpartum.…”
mentioning
confidence: 99%
“…In contrast to the results for HPV16, HPV18 and HPV58, a significant protective effect of HLA-B15 was observed for HPV52-positive cases. HPV52 has also been found in a relatively higher frequency in a few Asian cities including Japan, 25 China 26 and Taiwan 27 where HLA-B15 is also a common allele. It would be worthwhile to examine whether similar protective effect exists in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nested PCR amplification of a conserved region of the HPV L1 gene DNA with the consensus MY09/MY11 and GP5 + /GP6 + primers (Table 1), followed by genotyping with direct DNA sequencing [22][23][24][25], was used for HPV DNA detection. For primary PCR amplification, all specimens were first subjected to PCR amplification with HPV consensus primers MY09/MY11.…”
Section: Hpv Detection and Typing By Sequencingmentioning
confidence: 99%